Genetic polymorphism of dopamine D2 receptor (DRD2) and personality risk behaviour associated with drug addiction / Izuddin Fahmy Abu - Abu, Izuddin Fahmy (2009)
To investigate the types and frequencies of allelic variants of DRD2, drug injecting behaviours and personality traits among intravenous drug users (IVDUs) in Malaysia. Methods: Ninety-three IVDUs that met the inclusion and exclusion criteria were assessed with Diagnostic and Statistical Manual (DSM) of American Psychiatric Association Version IV (DSM IV), Tridimensional Personality Questionnaire (TPQ) and WHO Drug Injecting Study Phase II Questionnaire. DNA were extracted from subjects’ whole blood and then subjected to polymerase chain reaction (PCR) method to analyze the frequencies of DRD2 allelic variants among IVDUs.